The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/1553350610365346
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Alignment “Mirror Image” Visualization as a Laparoscopic Training Tool Improves Task Performance

Abstract: Reverse alignment (mirror image) visualization is a disconcerting situation occasionally faced during laparoscopic operations. This occurs when the camera faces back at the surgeon in the opposite direction from which the surgeon's body and instruments are facing. Most surgeons will attempt to optimize trocar and camera placement to avoid this situation. The authors' objective was to determine whether the intentional use of reverse alignment visualization during laparoscopic training would improve performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…This may simply reflect improvement in motor skills and increased familiarity with the equipment. Dunnican et al [12] conducted a similar study to ours and determined that training in reverse-alignment conditions resulted in the development of both forward-and reversealignment skills; however, forward-alignment training improved only forward-alignment performance. The reasons for this minor discrepancy between our studies are not clear, but we believe the central theme in each is that through training, surgeons can learn to adapt to reversealignment conditions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This may simply reflect improvement in motor skills and increased familiarity with the equipment. Dunnican et al [12] conducted a similar study to ours and determined that training in reverse-alignment conditions resulted in the development of both forward-and reversealignment skills; however, forward-alignment training improved only forward-alignment performance. The reasons for this minor discrepancy between our studies are not clear, but we believe the central theme in each is that through training, surgeons can learn to adapt to reversealignment conditions.…”
Section: Discussionmentioning
confidence: 69%
“…It has been demonstrated that training can improve an individual's ability to perform these mental rotations [10]. Researchers have found that the skills learned through training in mental rotation tasks are transferrable to tasks that are structurally different yet rely on similar mental processing [11,12]. Stransky et al [12] has shown that the skills learned through mental rotation training are also transferrable to certain FLS tasks performed in a video trainer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the MAGS camera had to be held off center so an appropriate view of the operative field could be obtained. It is well known that holding a camera off axis increases the psychomotor demands of a given task in a traditional multiport setting and results in a degraded task performance [25,[33][34][35][36][37]. For ex vivo testing, the experts seemed to compensate completely for this increased level of difficulty, whereas the fellows did not (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The comparison of other methods such as VR trainers with the BTs showed that differences were present in some of the measured outcomes. Nevertheless, these results were based on small randomized controlled trials and no specific conclusions could be drawn in the case of novice trainees .…”
Section: Hands‐on Training In Laparoscopy‐box Trainersmentioning
confidence: 99%